Effects of a nutraceutical combining green tea extract, vitamin C, D, and zinc in patients with post-COVID conditions - Chian-Yi Liu; Chih-Yu Hsieh; Shih-Heng Chang; Shu-Chuan Wang; Chih-Cheng Lin (Journal of Food Science and Nutrition Therapy - Peertechz Publications, 2023)
Tea and ascorbic acid have antioxidative and anti-inflammatory effects, and vitamin D and zinc have immunomodulatory effects. This study investigated the effect of a nutraceutical prescription combining these four nutrients on the blood biochemical markers and the modified C19-YRS questionnaires in patients who had recovered from COVID-19 disease for four months. Analysis of six markers associated with long COVID symptoms, i.e., INR, d-dimer, hs-CRP, NT-ProBNP, IL-6 and IgA, indicated that the nutraceutical could positively affect the values, especially for the inflammatory markers. The physician's clinical observation and questionnaire analysis reported significant improvements in post-exertional malaise, sleep quality and overall health of the patients. These results suggested that formulated nutraceutical could not only reduces or eliminates the symptom of long COVID, but potentially also prevents reinfection.